Language Learning and Emotional Growth: A Study of Preschool Children in Multilingual Contexts – Sudan - Amel Zulfukar Hassan Adlan; Khabir Othman Mohamed Badawi; Rose Chikopela (CV Media Inti Teknologi, 2026)
Background: The development of young children is greatly dependent on language exposure, but the relationship between multilingualism and socio-emotional development remains relatively unexplored with regard to Sudanese culture. Multilingualism in the Sudanese culture involves a combination of Arabic, English, and dialect, which can work as a tool to foster cognitive and emotional resilience in early childhood. Objective: This paper seeks to establish the role of multilingual settings in the development of cognitive flexibility and socio-emotional intelligence in preschoolers (3–5 years old) enrolled in the Noor Albayan Kindergarten in Atbara, Sudan. Methods: Through the use of convergent parallel mixed methods research design, the study conducted a quantitative assessment of 25 children (N=25) using Sort-Switch tasks. The quantitative data obtained were subjected to analysis through one sample t-tests (df=24). On the other hand, qualitative data were obtained by conducting semi-structured interviews involving 10-12 key informants (teachers and parents). Results: Analysis of the quantitative data showed that multilingual children scored 72% on problem-solving tasks (t (24) =9.17, p<.001). Additionally, they scored 68% on social adaptation skills (t (24) =6.43, p<.005) and 65% on emotional awareness tasks (t (24) =5.00, p<.005). Moreover, qualitative data showed. Conclusion: These results indicate that bilingualism speeds up the development of prefrontal cortex and emotional differentiation. The findings of this paper recommend the application of translanguaging practices in Sudanese Early Childhood Education (ECE).